ARVs and ARTs: Medicoscapes and the Unequal Place‐making for Biomedical Treatments in sub‐Saharan Africa. (21st April 2014) - Hörbst, Viola; Wolf, Angelika
<x xml:space="preserve">Abstract</x> Asking why some diseases gain global attention whereas others are neglected, we present two case studies that demonstrate the unequal treatment and financing options available for HIV/AIDS versus infertility treatments. We track three key phenomena central to understanding the unequal public attention given to certain ailments: peace and security, subordination of the social to the biological, and a "global" quality. Existing concepts such as global assemblages or therapeutic citizenship are quite limited when it comes to bodily conditions that result in social suffering and do not satisfy the conditions of advocacy. Since it is not enough to observe "flowing" and "moving, " we propose the concept of medicoscapes, to acknowledge that such activities simultaneously entail channeling and carving out. Medicoscapes enhance the analysis of linkages between different health conditions regardless of whether they are biological or social and how they interconnect places, sites, and people.